DO INSTITUTIONAL AND POLITICAL REFORMS MATTER TO CUSTOMS COLLECTION? EVIDENCE FROM INDONESIA - Rifa'i, Achmad (Politeknik Keuangan Negara STAN, 2019)
Sustainable development requires resources that are not small, especially in terms of funding. The government has always tried to maintain the state revenue post as a form of business to become a sovereign state through financing strategic projects through state revenues. Customs and Excise is one of the main components that are a source of development funding. Several issues related to reform in the government sector were carried out to improve the management of the country including in order to increase customs and excise revenues. This research focuses on analyzing the issue of reform which has become the spirit of the government in collecting customs and excise. The model used in this study is the Error Correction Model (ECM). Based on empirical results show that several institutional and political reform proxies play an important role in increasing customs and excise revenues. In addition, several issues for further research in the future are delivered to further refine the analysis.